Graphene-water nanofluid in heat exchanger: Mathematical modelling, simulation and economic evaluation. (November 2019) - Purbia, Devendra; Khandelwal, Akshya; Kumar, Amit; Sharma, Arvind Kumar
Abstract: The snowballing demand for energy all over the world is driving the researchers to develop an energy efficient heat exchanger system. Although nanofluids play a vital role in the enhancement of its thermal performance, they also increase the pressure drop in the system. Therefore, in this work graphene oxide is adopted as a nanoparticle and is compared with the conventional nanoparticles like Al 2 O 3 and TiO 2 . The modelling and simulation for two-dimensional steady-state momentum transfer and heat energy consumption, have been done using MATLAB R2018b. The base fluid considered is pure water and concentrations of nanoparticle are 0.025%, 0.05%, 0.075%, 0.1% respectively. The fluid flow is assumed to be turbulent and the temperature is taken in the range of 20 ∘ C to 70 ∘ C. Multifarious parameters like Nusselt number, Peclet number, friction factor, pressure drop and convective heat transfer coefficient are calculated and discussed. The results originated from the simulation are in good agreement with the experimental results reported in the literature. To find the overall applicability of graphene-water nanofluid, the potential benefits of the nanofluids are also estimated, and it is found that one of the benefits of using graphene-water nanofluid will be the dramatic reduction in the operating cost of heat exchanger system. It is also investigated that the graphene-water nanofluid can highly augment the thermal performance of heat exchanger systems which can undermine the adverse effect of pressure drop.